Pengaruh Jenis Pupuk dan Dekomposer terhadap Pertumbuhan dan Produksi Padi Organik - Arinal Haq Izzawati Nurrahma; Maya Melati (Departemen Agronomi dan Hortikultura, 2013)
The objective of the research was to study the effect of fertilizer types and decomposer on growth and yield of organic rice Field experiment was carried out in Cikarawang, Dramaga, Bogor from November 2011 to March 2012. The experiment used factorial-randomized complete block design with fertilizer combinations (15 ton chicken manure ha-1and 5 ton Tithonia diversifolia ha-1, 10 ton chicken manure ha-1 and 5 ton T. diversifolia ha-1, and 10 ton chicken manure ha-1 and 5 ton rice straw ha-1) as the first factor and decomposer application (using decomposer and without decomposer) as the second factor. Organic fertilizer types significantly affected root wet weight, nutrient content of P and K in leaves. Rice yields were not significantly different with fertilizer combinations 15 ton chicken manure ha-1 and 5 ton T. diversifolia ha-1, 10 ton chicken manure ha-1 and 5 ton T. diversifolia ha-1, and 10 ton chicken manure ha-1 and 5 ton rice straw ha-1, they were 2.28, 2.22, and 2.16 ton dry seed ha-1, respectively. Decomposer application significantly affected the number of tillers at 8 week afterplanting, leaf color at 5 weeks after planting, nutrient content of P in leaves and panicle length. Rice yield with decomposer application and without decomposer were 2.25 and 2.19 ton ha-1, respectively, and they were not different.Keywords: chicken manure, decomposer, organic rice, rice straw, Tithonia diversifolia